Network disruption detected in SS (South Sudan) - Voidly (2026)
CRITICAL severity disruption detected in South Sudan. Confidence: 70%. Data sourced from IODA.
Network Disruption Incident ID: SS-2026-0003
Keywords: internet disruption; SS; disruption; critical